2020
DOI: 10.1002/sej.1352
|View full text |Cite
|
Sign up to set email alerts
|

When do return migrants become entrepreneurs? The role of global social networks and institutional distance

Abstract: Research Summary: Does embeddedness in global social networks elevate or diminish individuals' propensity to found new ventures? I analyze entrepreneurial entry among a large, cross-country sample of skilled return migrants, all of whom had worked abroad in the United States before returning to 98 different home countries. My findings reveal that maintaining stronger cross-border social ties-that is, relationships to former colleagues abroad-leads returnees to be more likely to found new ventures in their home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…They cannot explain why some individuals are more likely to launch new ventures or become self-employed, while others do not. Finally, though there is a small yet growing literature on “returnees” (e.g., Bai et al., 2017 ; Liu and Almor, 2016 ; Wang, 2020 ), extant research in this domain typically focuses on entrepreneurial activity in a domestic context by those from a foreign context ( Liu et al., 2010 ). We still lack understanding of how the exposure to foreign countries in-itself fosters entrepreneurial mindsets, regardless of where businesses eventually take root.…”
Section: A Schema Theory Modelmentioning
confidence: 99%
“…They cannot explain why some individuals are more likely to launch new ventures or become self-employed, while others do not. Finally, though there is a small yet growing literature on “returnees” (e.g., Bai et al., 2017 ; Liu and Almor, 2016 ; Wang, 2020 ), extant research in this domain typically focuses on entrepreneurial activity in a domestic context by those from a foreign context ( Liu et al., 2010 ). We still lack understanding of how the exposure to foreign countries in-itself fosters entrepreneurial mindsets, regardless of where businesses eventually take root.…”
Section: A Schema Theory Modelmentioning
confidence: 99%
“…This desire motives them to be more proactively engaged in identifying international opportunities and making efforts to exploit such opportunities (He et al, 2020). Given that cross-border network ties allow access to foreign market knowledge and information that might not available in home country markets (Wang, 2020), we expect that returnee entrepreneurs with a global mindset are more willing to learn from people in their cross-border networks and more proactively interact with such network members to seek every possible opportunity in foreign markets. This argument is supported by Vanninen et al (2017), who found that individuals with a global mindset tend to more proactively socialize with network members in target markets in order to explore opportunities abroad.…”
Section: The Moderating Role Of Global Mindsetmentioning
confidence: 99%
“…Second, much of the literature shows that the cross-border network is the main advantage of returnee entrepreneurs compared with local entrepreneurs, and returnees often rely on such networks to acquire diverse resources and knowledge (Dai and Liu, 2009;Liu et al, 2010;Ma et al, 2019;Wang, 2020). Although this research line documents the importance of crossborder networks for firm creation and performance, other work suggests that networks across national boundaries may lose their value (Welch and Welch, 2008), and in fact, returnees encounter difficulties in mobilizing such networks due to institutional distances Cross-border network ties' impacts between host country and home country and decreased regular interactions caused by geographically remote distances (Lin et al, 2019;Prashantham and Dhanaraj, 2010;Pruthi, 2014).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interconnectedness of the global economy and ever-changing technological innovations, on which developed countries no longer hold dominant positions (National Research Council, 2012), has spurred the rise of entrepreneurs globally and leveled the competition field even further. Studies have found cross-border social networks have been the key to the entrepreneurial success of the returnees (Wang, 2020). Such migration of people, markets, technologies and ideas has combined with increasing entrepreneurial activities that undoubtedly shrink the economic or social development gaps of the world.…”
mentioning
confidence: 99%